2015
DOI: 10.1186/s12889-015-1487-x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of premature mortality in Poland analysed with the use of standard expected years of life lost

Abstract: BackgroundDespite positive changes in the health of the population of Poland, compared to the EU average, the average life expectancy in 2011 was 5 years shorter for males and 2.2 years shorter for females. The immediate cause is the great number of premature deaths, which results in years of life lost in the population. The aim of the study was to identify the major causes of years of life lost in Poland.MethodsThe analysis was based on a database of the Central Statistical Office of Poland, containing inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 22 publications
3
46
1
4
Order By: Relevance
“…In general, our results for AYLL were high when compared to international reports, which inform of less than 7 years AYLL for colorectal and breast cancer (USA), 1.8 for prostate cancer, and 13.8 for lung cancer (6,7,16). In a Polish study, only male brain cancer and cervical cancer showed more than 10 years of life lost per death (AYLL 10.7 and 10.2, respectively) (16).…”
Section: Discussionsupporting
confidence: 43%
“…In general, our results for AYLL were high when compared to international reports, which inform of less than 7 years AYLL for colorectal and breast cancer (USA), 1.8 for prostate cancer, and 13.8 for lung cancer (6,7,16). In a Polish study, only male brain cancer and cervical cancer showed more than 10 years of life lost per death (AYLL 10.7 and 10.2, respectively) (16).…”
Section: Discussionsupporting
confidence: 43%
“…This finding suggested an epidemiological transition of diseases from communicable to non-communicable diseases as in all other developed and developing countries (7,25,(27)(28)(29). Chronic diseases are no longer only a problem of the developed world because it was reported that more than 80% of deaths due to chronic diseases took place in low and middle income countries (7,24,25,(27)(28)(29). Similarly, the National Burden of Disease Study of Turkey, 2004 and the Turkey Prevalence of Chronic Diseases and Risk Factors Study reported a silently rising epidemic of non-communicable diseases in our country; the results of this study support the findings of that population-based study, which was carried out in 2013 (18,22).…”
Section: Resultsmentioning
confidence: 79%
“…Another important finding of this study is the dramatic increase in the percentage of SEYLL due to chronic non-communicable diseases such as cardiovascular system diseases (34.7% to 41.2%), neoplasms (12.5% to 14.6%) and respiratory system diseases (6.2% to 9.8%), and the dramatic decrease in the percentage of SEYLL due to infectious and parasitic diseases (6.6% to 3.7%). This finding suggested an epidemiological transition of diseases from communicable to non-communicable diseases as in all other developed and developing countries (7,25,(27)(28)(29). Chronic diseases are no longer only a problem of the developed world because it was reported that more than 80% of deaths due to chronic diseases took place in low and middle income countries (7,24,25,(27)(28)(29).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Struktura ludności według wieku i płci stanowi istotny element większości analiz demograficznych i stanu zdrowia populacji, gdyż nie tylko determinuje kształto-wanie się przyszłych trendów w zakresie umieralności, ale także daje podstawę do określenia wielu konsekwencji uwarunkowań społeczno-ekonomicznych sytuacji zdrowotnej (Holzer, 2003;Bryła, Burzyńska, Maniecka-Bryła, 2013;Burzyń-ska i in., 2016;Maniecka-Bryła i in., 2015). W Polsce, podobnie jak w innych krajach, występuje nadumieralność męż-czyzn, jednak skala tego zjawiska jest znacznie wyższa.…”
Section: Podsumowanieunclassified